Energy, Poverty, and Health in Climate Change: A Comprehensive Review of an Emerging Literature - Jessel, Sonal; Sawyer, Samantha; Hernández, Diana (Frontiers in Public Health, 2019)
Household energy is increasingly vital for maintaining good health. Unaffordable and inadequate household energy presents adverse consequences that are amplified by poverty and a changing climate. To date, the connections between energy, socioeconomic disadvantage, and wellbeing are generally underappreciated, and its connection to climate change is under researched.Building on the energy insecurity framework, this review explores literature related to household energy, poverty and health in order to highlight the disproportionate burdens borne by vulnerable populations in adequately meeting household energy needs. This paper is based on a comprehensive review of books, peer-reviewed articles, and reports published between 1990 to 2019 identified via databases including JSTOR, and PubMed. A total of 406 publications were selected as potential for a full review, 203 received full review, and 159 were included in this paper on the basis of set inclusion criteria.From the literature review, we created an original heuristic model that describes energy insecurity as either acute or chronic and further explore the mediators and pathways that link energy insecurity to health. In the discussion, we posit that extant literature does not sufficiently consider that vulnerable communities often experience energy insecurity bundled with other hardships. We also discuss energy, poverty, and health through the lens of climate change, critiquing that most research on household energy does not consider climate change. This evidence is important for enhancing research in this field, and developing programmatic and policy interventions as they pertain to energy access, affordability and health with special emphasis on vulnerable populations, climate change and social inequality.